Total Propagated Uncertainty (TPU) for Hydrographic LiDAR to Aid Objective Comparison to Acoustic Datasets - Lockhart, Carol; Lockhart, Doug; Martinez, José (The International Hydrographic Review, 2008)
Previously, when comparing LiDAR datasets to other LiDAR or acoustic datasets, comparisons have always presumed that one control dataset is ultimately correct, with no errors. All error is attributed to the second dataset. Surface and target analysis methods have therefore been somewhat subjective. The use of TPU takes into account the fact that each depth point is an estimate with an associated uncertainty. This paper discusses a method to derive TPU for LiDAR sensors, so that CUBE may be used to perform an objective comparison of LiDAR bathymetry and acoustic datasets.